Kepatuhan Wajib Pajak Dari Sudut Pandang Pengetahuan Pajak, Kualitas Pelayanan, Sanksi Pajak: Pemoderasi Preferensi Risiko - Mei, Magdalena; Firmansyah, Amrie (E-Jurnal Akuntansi, 2022)
In developing countries such as Indonesia, related problems such as taxation are deficient taxpayer compliance and a high level of tax manipulation (pajak.go.id). This study aimed to obtain empirical evidence of the effect of tax knowledge, service quality and perceptions of tax sanctions on taxpayer compliance. In addition, this study uses risk preference as a moderating variable in testing the relationship between the independent and dependent variables. The data collection technique was carried out using a survey method using a questionnaire that was distributed directly to the respondents. Hypothesis testing is done by using structural equation modelling. The study results conclude that tax knowledge and perceptions of tax sanctions positively affect taxpayer compliance, while service quality has no effect on taxpayer compliance. Furthermore, risk preference can weaken the positive perception of tax sanctions on taxpayer compliance. Meanwhile, risk preference does not moderate the relationship between tax knowledge and taxpayer compliance and the relationship between service quality and taxpayer compliance. Keywords: Tax Knowledge; Service quality; Tax Sanctions; Tax Compliance; Individual Taxpayers; Risk Preference